Characterizing flexural behaviour of panel-to-panel connections in cross-laminated timber floor systems. (December 2020) - Zhang, Sigong; Chui, Ying Hei
Abstract: Cross-laminated timber floor systems are currently designed by treating them as one-way systems. The one-way assumption is conservative but two-way model would overestimate the system stiffness if the presence of semi-rigid panel-to-panel connections is not properly considered in the analysis. These connections allow for partial transfer of bending moment from one panel to the adjacent panel. The primary objective of this research was to characterize the flexural behaviour of typical panel-to-panel connections used in cross-laminated timber floors. Two types of connections employing self-tapping screws and surface splines were examined through testing. The resulting bending moment versus rotation curves were used to determine the rotational stiffness and moment capacity of connection assemblies. The influences of screw quantity, screw diameter and length, and spline thickness on connection stiffness and capacity were studied. Test results indicated that the flexural properties were significantly dependent on the number of screws used in the connection. Screw diameter and spline thickness also influenced flexural performance but to a less extent. However, the longer screws resulted in smaller stiffness and capacity with high variability for butt joints. It was found that the capability of moment transfer is very limited for these tested connections and less than 6% rotational stiffness was achieved by comparing with those of intact beams. A secondary objective of the research was to evaluate the experimental procedure developed for this research to measure flexural properties of panel-to-panel connection. Overall, the experience and results indicate that the experimental procedure used was practical.